Leptin Induces an Inflammatory Phenotype in Lean Wistar Rats - Monique Allman; Mathew Wallace; Latausha Gaskin; Chantal A. Rivera (Mediators of Inflammation)
The present study addressed the hypothesis that leptin promotes leukocyte trafficking into adipose tissue. Accordingly, male Wistar rats were treated with saline or recombinant rat leptin (1 mg/kg) via the tail vein. Leukocyte trafficking in mesenteric venules was quantified by intravital microscopy. Treatment with leptin resulted in a 3- and 5-fold increases in rolling and firm adhesion, respectively. Compared to vehicle controls, leptin enhanced mRNA levels of IL-6 (8-fold) and MCP-1 (5-fold) in mesenteric adipose tissue (MAT). Similar increases in these markers were observed in mesenteric venules and in liver. Finally, the direct effect of leptin was assessed in C3A hepatocytes treated with leptin for 24 hours (7.8 ng/mL–125 ng/mL). Consistent with observations in vivo, production of ICAM-1, MCP-1, and IL-6 by hepatocytes was increased significantly. These findings support the hypothesis that leptin directly initiates inflammation in the local environment of mesenteric adipose tissue as well as systemically.